Barriers Faced by Small Scale Farmers in the North Department of Haiti - Bertrhude Albert; Grady T. Roberts; Amy Harder (Journal of International Agricultural and Extension Education, 2017)
Haiti is one of the economically poorest countries in the world. As a result, billions of dollars have been invested into agricultural initiatives in Haiti, however, less emphasis has been placed on building the capacity of farmers through training and educational programs. Limited research has been conducted on barriers faced by Haitian farmers. The purpose of this study was to explore the barriers and faced by small scale farmers in the North Department of Haiti. A qualitative approach was used to achieve this purpose. Results revealed 11 major barriers, organized in the two themes of environmental challenges and resource limitations. Emergent themes included an external locus of control as a cause of barriers. Based on findings, recommendations for practice and future research are provided. Lessons learned from this research can help extensionists in Haiti and similar locations better meet the needs of farmers.
Keywords: barriers; farmer; training; Haiti; agriculture